Peran Keluarga Dengan Kepatuhan Minum Obat Pada Pasien TB Di Wilayah Kerja Puskesmas - Zulkahfi, Zulkahfi; Hadi, Irwan; Halid, Sopian; Maliki, Imam (Barongko: Jurnal Ilmu Kesehatan, 2024)
Tuberculosis (TB) is an infectious disease with the highest death cases in the world. One of the things that causes is the low role of the family in drug adherence. This study aims to determine the relationship between family roles and medication adherence in TB patients. The design used in this research is an analytical correlation with a retrospective approach. The number of samples in this study is 37 respondents. The results of the chi square statistical test obtained a p value = 0.0005 or p < 0.05. H1 is accepted and H0 is rejected which means there is a relationship between the role of the family and adherence to TB medication the recommendations that can be given are the provision of counseling and health promotion activities about the importance of family support for the success of OAT therapy treatment.